Historiographical Transformation in the Chronicles of 14th-century Bohemia: A Case Study of Břetislav I - Szilárd Kováč (Ceræ)
There is no doubt that Břetislav I (1005–1055) was one of the most important princes of the early history of the Přemysl dynasty. The earliest Czech chronicler, Cosmas of Prague, attributes to him not only outstanding successes and reforms, but also sees him as the saviour of the Přemyslid dynasty and the embodiment of the virtues attributed to rulers. It was therefore only natural that almost three hundred years later, when Charles IV commissioned the 'official' Czech court chronicle of the Luxembourg dynasty, Břetislav I was not absent. However, the narratives of the fourteenth-century sources show a surprising and radical departure from Cosmas, whose chronicle was certainly their main source. My research compares Cosmas' narrative with that of Přibík Půlkava, the most successful and important author of Charles IV's great historiographical project, as well as with the chronicle of the so-called Dalimil, a source written outside the court culture in Old Czech. In my paper I will discuss a case study of this comparative research, the relationship between Břetislav I and the Přemysl dynasty, consisting of the depiction of his illegitimate origin and his dynastic marriage with Judith of Schweinfurt.